Evaluation of the effect of desensitizing agents on the retention of complete cast crowns: An in vitro study - Arun Prakash Chandrasekaran; Nargunan Deepan; Bharath Karikurve Rao; Swathi Pai; Abhay Sonthalia; Swapna Venkatesh Bettanpalya (Wolters Kluwer Medknow Publications, 2014)
Purpose: Dentin desensitizing agents are commonly used in dental practice. But their effect on crown retention have been anecdotal. This study compared and evaluated the effect of two desensitizing agents on the retention of cast crowns cemented with three commonly used luting cements. Materials and Methods: Recently extracted 81 maxillary first premolars were prepared with flat occlusal surface, 6-degree taper and 4-mm axial height using a custom made paralleling milling device. The prepared teeth were divided into three major groups and further sub-divided into three groups each. GC Tooth Mousse and Seal and Protect were two desensitizing agents. Zinc Phosphate cement, Glass Ionomer Cement and Resin Modified Glass Ionomer Cement were the three cements used. Impressions of the prepared teeth were made and casted with a loop using base metal alloy. The desensitizers were applied on the tooth except the control group, castings were cemented, thermo-cycled and removed along the path of insertion using a universal testing machine. The results were analyzed using Kruskal - Wallis test and Mann - Whitney U test. Results: Resin Modified Glass Ionomer Cement exhibited highest retentive strength of all tested group and Zinc phosphate cement being the least. Retentive strength for Resin modified Glass Ionomer Cement was, Control>with Tooth Mousse> with Seal and protect. For Glass Ionomer Cement, Control > with Tooth Mousse > with Seal and Protect. The lowest of retentive strength was for Zinc phosphate which were Control > with Seal and Protect > with Tooth Mousse. Conclusion: The use of Tooth Mousse desensitizer significantly reduced the retention of Zinc Phosphate. Both tooth mouse and Seal and protect did not affect the retentive property of Glass Ionomer cement and Resin Modified Glass Ionomer Cement significantly, hence can be advocated to use prior to crown cementation.